Analisis Elemen Sukses Pengembangan Layanan Publik berbasis E-Government di Kota Padang - Widya Cancer Rusnita; Desna Aromatica; Roni Ekha Putera (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2023)
The concept of e-government has become a trend and solution for improving the quality of public services that are effective and efficient in the industrial era 4.0. Since 2018 Padang City has made efforts to accelerate e-Government since it was designated as 1 of 100 smart cities by the central government. The Government of Padang City has launched quite a few digital-based innovations supported by policies and increased human resources. The purpose of writing this article is to analyze the development of e-government in Padang City using the theory of three elements of successful e-government development by the Harvard JFK School of Government. The research method uses descriptive qualitative. The results of the study show that in general, the development of e-Government in Padang City is going well, as evidenced by the existence of a number of legal products to support the implementation of e-Government, sustainable planning, and benefits felt by the government and society. However, there are still a number of obstacles including a lack of human resources who have skills in the ICT field, the servers are not accompanied by adequate security, and budget constraints to improve the quality of e-Government application development.Keywords: Public Service; e-government; Padang city AbstrakKonsep e-Government telah menjadi trend dan solusi untuk peningkatan kualitas pelayanan publik yang efektif dan efisien di era industry 4.0. Sejak tahun 2018 Kota Padang melakukan upaya percepatan e-Governmnent sejak ditetapkan sebagai 1 dari 100 kota smart city oleh pemerintah pusat. Pemerintah Kota Padang cukup banyak meluncurkan inovasi berbasis digital yang didukung oleh kebijakan serta peningkatan sumber daya. Tujuan penulisan artikel ini adalah untuk menganalisis pengembangan e-Government di Kota Padang menggunakan teori tiga elemen sukses pengembangan e-Government oleh Harvard JFK School of Government. Metode penelitian menggunakan kualitatif deskriptif. Hasil penelitian menunjukkan bahwa secara umum pengembangan e-Government di Kota Padang berjalan dengan baik, yang dibuktikan dengan adanya sejumlah produk hukum untuk mendukung penerapam e-Government, perencanaan yang bersifat berkelanjutan dan kebermanfaatan yang dirasakan oleh pemerintah dan masyarakat. Namun masih terdapat beberapa kendala diantaranya masih kurang SDM yang memiliki skill di bidang TIK , server belum disertai dengan keamanan yang memadai serta keterbatasan anggaran untuk meningkatkan kualitas pengembangan aplikasi layanan publik e-Government.Kata Kunci: Layanan Publik; E-government; Kota Padang